Pengaruh Kepuasan Kerja, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Toko Nyu Nyu All Shop di Mojosongo - Dila Syamsiah, Nurani; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Nyu-Nyu All Shop, an imported clothing and accessories retail business that has been operating since 2014 with 30 employees. The store is located on Jalan Jaya Wijaya, Mojosongo, Jebres District, Surakarta City, Central Java. This study aims to analyse the influence of job satisfaction variables, work motivation, and work discipline on employee performance at the store. This study, by taking a sample of all employees (N=30), aims to empirically test the effect of job satisfaction variables, work motivation, and work discipline on employee performance in the company. Data analysis was conducted using SmartPLS software with descriptive analysis techniques, construct validity test (convergent and discriminant), reliability test, prediction test (Q2), hypothesis test (t test), goodness of fit test, and coefficient of determination (R2) analysis. Convergent validity analysis shows that the research instrument has met the validity criteria after deleting several items. The results of the discriminant validity test with the Heterotrait-Monotrait method (HTMT) also indicate that the constructs in this study are valid. The regression analysis results show that the independent variables in this study, namely job satisfaction, work motivation, and work discipline, are collectively able to explain 89% of the variance in employee performance (R-Square = 0.890). Hypothesis testing shows that there is a significant influence between work motivation and work discipline on the performance of Nyu-Nyu All Shop employees, with a positive direction of influence. In contrast, the effect of job satisfaction on employee performance is not significant and has a negative direction.